THORETICAL ANALISES POSIBLITIES FORMATION OF SPIRAL-SHAPED AND EXOTIC GALAXIES WITH THE INFLUENCE OF BLACK HOLES - Melibayev Muxtardjan (Galaxy International Interdisciplinary Research Journal, 2024)
This work examines the structure and process of evolution of disk-shaped galaxies, as well as the question of the existence of exotic galaxies.